2015
DOI: 10.4081/vsd.2015.5977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of opportunistic fungi and their possible role in postpartum endometritis in dairy cows

Abstract: The aim of this study was to identify fungal infections by culture from uterine lavages of 172 Holstein dairy cows between 25 and 35 days postpartum and two weeks later. In the first examination, 61/172 (35.5%) cows were suffering from clinical endometritis. The positive rate of fungal growth was fifteen (8.7 %) swabs and the remaining 157 (91.3%) showed no fungal growth. The most frequently isolated fungi were <em>Aspergillus</em> spp. (60%) followed by <em>Penicillium</em> spp. (26%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…In one study, for instance, endometritis was recognized in up to 40% of the postpartum cows by vaginoscopic examination (De Kruif, Gunnink, & Bois, ). In another study, wherein the method of diagnosis was similar to the present, the incidence of endometritis was 35.5% (Derakhshandeh, Aghamiri, Ahmadi, & Mirzaei, ). Because there is no consistent definition or diagnostic consensus regarding CE, the incidence is different in various studies.…”
Section: Discussionsupporting
confidence: 60%
“…In one study, for instance, endometritis was recognized in up to 40% of the postpartum cows by vaginoscopic examination (De Kruif, Gunnink, & Bois, ). In another study, wherein the method of diagnosis was similar to the present, the incidence of endometritis was 35.5% (Derakhshandeh, Aghamiri, Ahmadi, & Mirzaei, ). Because there is no consistent definition or diagnostic consensus regarding CE, the incidence is different in various studies.…”
Section: Discussionsupporting
confidence: 60%
“…In the study conducted by [26], Figure 1 illustrates the utilization of multiplex PCR to detect pathogenic bacteria. Furthermore, Derakhshandeh et al reported the presence of fungi and yeast in uterine samples from cows with endometritis [27]. Similar findings were reported in studies involving repeat breeder cows by [28,29].…”
Section: Theriogenology -Recent Advances In the Fieldsupporting
confidence: 72%
“…The presence of multidrug resistance in species such as Trueperella pyogenes and E. coli [24,86] and the occurrence of antibiotic residues in milk after intrauterine infusion of oxytetracycline (OTC) [87,88] have raised concerns. It has been observed that intrauterine infusion of antibiotics like OTC may increase the incidence of mycotic endometritis [27].…”
Section: Treatment Of Subclinical Endometritismentioning
confidence: 99%
“…in cattle and buffalo. Derakhshandeh et al (2015) reported 8.7% (25-35 days postpartum) and 5.5% (39-49 days postpartum) prevalence of mycotic endometritis in Holstein cattle, and the most frequently isolated fungus was Aspergillus spp. (60.0%), Penicillium spp.…”
Section: Introductionmentioning
confidence: 99%